OPTIMIZATION, DEVELOPMENT, AND SAFETY EVALUATION OF OLIVE OIL NANOEMULSION FOR TOPICAL APPLICATION: A RESPONSE SURFACE METHODOLOGY - Wan Ishak, Wan Maznah; Zulfakar, Mohd Hanif (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Nanoemulsions consist of fine oil-in-water dispersions, with droplets covering the size range of 50–500 nm. Olive oil is frequently utilized in cosmetic and pharmaceutical topical product for its healing, protecting, and moisturizing properties due to its high fatty acid and antioxidant content. In the present work, a nanoemulsion composed of olive oil, Span 80 as surfactant, and Labrasol as cosurfactant was developed using a high-pressure homogenization method and was evaluated for its physicochemical characteristics. Methods: Response surface methodology was utilized to investigate the influence of the main nanoemulsion components: olive oil (X1), Span 80 (X2), and Labrasol (X3) on the droplet size (Y1) and polydispersity index (PDI) (Y2). A total of 17 formulations were generated by the Box-Behnken model. Results: The model was found to be highly significant with R2 values of 0.9833 and 0.9382 for droplet size and PDI, respectively. The optimized nanoemulsion presented the droplet size of 144.2±0.8 nm and PDI of 0.105±0.014. Span 80 seems to be the most influential factor that determines the droplet size as it has higher significant linear and interaction effects. The developed nanoemulsion was, further, evaluated with an in vivo skin irritancy study using the rat model. Conclusion: Results indicate that the developed nanoemulsion did not demonstrate any skin irritations in gross and histological examinations, suggesting that it is safe for topical applications.